Effects on Inventory Model in Time Deteriorate Rate with Variable Cost - Khare, Garima; Sharma, Garima (International Journal of Intelligent Systems and Applications in Engineering, 2022)
This paper anticipates showing the optimistic a reflection of an inventory model employing quadratic demand, scarcity allows, and time-dependent with varying degradation rate with ordering and storage cost. The impact of such criteria on the total cost of the inventory will be evaluated. The conceptual frameworks are then illustrated by numerical examples, and sensitivity analysis of the key variables affecting the appropriate solution is also performed.